Organizational innovation: verifying a comprehensive model for catalyzing organizational development and change - Annika Steiber; Sverker Alänge (Triple Helix, 2015)
In a rapidly transforming global marketplace, organizations need to make effective use of organizational innovations in order to remain competitive. Previous research has identified a need for a more comprehensive framework that will aid in better understanding of the mechanisms catalyzing organizational development and change. Steiber and Alänge (Triple Helix 2(9):1-25, 2015) presented such a comprehensive model for organizational innovations based on literature reviews and two empirical studies of the organizational innovations of Total Quality Management, Lean Production, and the Toyota Production System. All of these draw heavily on the experiences of Toyota in Japan and are known for their focus on continuous improvement of quality and efficiency.
Keywords: 330; Creation; Diffusion; Google; Organizational development; Organizational innovation; Sustaining